Pengaruh Model Pembelajaran Kooperatif Tipe NHT (Numbered Head Together) Berbantuan Ice Breaking terhadap Minat Belajar Siswa - Ni Kadek Asri Rumiartini (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research is an action to find out the influence of the NHT learning model assisted by Ice Breaking on the Learning Interest of Class XI C.1 Students of SMA Negeri 1 Kuta Utara. This classroom action research conducts a reflective action in order to improve learning practices for students in terms of professionalism. In this class action research, the subject of the study is students of class XI C1 SMA Negeri 1 Kuta Utara for the 2023/2024 school year consisting of 38 students. The score of 55.59 (low category) shows the results of the analysis of the first cycle. It is clear that students' interest in learning is still relatively low and there needs to be a big improvement in the second cycle. The score of 89.1 (very high category) was shown in cycle II after a careful analysis of the improvements in cycle I. So from the data obtained and processed in cycles I and II, it can be concluded that there is an influence in mathematics learning with the application of the Numbered Head Together type cooperative learning model assisted by Ice Breaking.